TEACHERPRENEURSHIP : Persepsi Mahasiswa Tarbiyah IAIN Kudus tentang Teacherpreneurship - Khoeroni, Farid (Institut Agama Islam Negeri (IAIN) Kudus, 2019)
AbstractThe purpose of this study was to determine the perceptions of Tarbiyah IAIN Kudus students and to find out teacherpreneurship reinforcement in the curriculum according to students. This study uses descriptive qualitative methods. The sources of data in this study are: Informants or resource persons, namely Tarbiyah students of Holy IAIN. The data collection technique used in this study was in depth interviewing. The data analysis technique used in this study is an interactive analysis model (Interactive Model of Analysis) which has three components, namely: data reduction, data presentation and drawing conclusions and verification. Based on the results of the study it can be concluded: (1) Perception of the Tarbiyah IAIN Kudus students is teacherpreneurship is something that is still considered positive, provided that the main work as an educator is not disrupted by the side job of being an entrepreneur. (2) Strengthening the entrepreneurship curriculum in its implementation is not only the theory taught in entrepreneurship courses, but there are also entrepreneurial practices to supplement the knowledge gained through the theory.Keywords: Perception, Teacher, Entrepreneur